2016
DOI: 10.1186/s40694-016-0019-5
|View full text |Cite
|
Sign up to set email alerts
|

Simple sequence repeat markers that identify Claviceps species and strains

Abstract: Background: Claviceps purpurea is a pathogen that infects most members of Pooideae, a subfamily of Poaceae, and causes ergot, a floral disease in which the ovary is replaced with a sclerotium. When the ergot body is accidently consumed by either man or animal in high enough quantities, there is extreme pain, limb loss and sometimes death.Results: This study was initiated to develop simple sequence repeat (SSRs) markers for rapid identification of C. purpurea. SSRs were designed from sequence data stored at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 32 publications
2
27
0
1
Order By: Relevance
“…The transcriptional activation of secondary metabolite (SM) gene clusters in different filamentous fungi is one current focus of the fungal research community (16) as >60% of currently approved clinical drugs are derived from natural products (59). A. niger stands out due to its exceptional high number of predicted SM gene clusters in its genome (n = 78), harboring 81 core enzymes in total, such as NRPS and PKS (39).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transcriptional activation of secondary metabolite (SM) gene clusters in different filamentous fungi is one current focus of the fungal research community (16) as >60% of currently approved clinical drugs are derived from natural products (59). A. niger stands out due to its exceptional high number of predicted SM gene clusters in its genome (n = 78), harboring 81 core enzymes in total, such as NRPS and PKS (39).…”
Section: Resultsmentioning
confidence: 99%
“…More recent sequencing of additional A. niger strains and other genomes from the genus Aspergillus (4–9), combined with refinement of online genome analyses portals (10–12), and comparative genomic studies amongst the Aspergilli (5,13–15), have not significantly increased the percentage of A. niger genes that have functional predictions. While the exact number of ‘hypothetical’ genes varies between databases and A. niger genomes, recent estimates suggest that between 40 and 50% of the genes still remain hypothetical (1,16). Furthermore, only 2% of its genes (n = 247) have a verified function in the Aspergillus Genome Database (AspGD (17)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. paspali ILB432 was isolated from sclerotia obtained from Paspalum urvillei -infected inflorescences collected near Portezuelo, Maldonado, Uruguay (global positioning system coordinates 34.888591S, 55.030316W), using a previously reported C. paspali isolation procedure ( 5 ). ILB432 was cultured at 26°C on Claviceps medium containing 36 g/liter potato dextrose agar, 2 g/liter yeast extract, 10 g/liter malt extract, 10 g/liter sucrose, and 5 g/liter agar ( 6 ). Phylogenetic analysis based on the partial gene coding for the second largest subunit of RNA polymerase subunit II ( RPB2 ) showed that ILB432, like reference isolate RRC-1481, belongs to the most frequent lineage of C. paspali ( 5 ).…”
Section: Announcementmentioning
confidence: 99%
“…Primer development for SSRs is easy and is commonly used between individuals because the flanking regions of microsatellites are well conserved (Vieira et al, 2016). To date, SSRs of various plant pathogens, including several fungal species with biphasic life cycles, have been developed for genetic studies (Della, Eyre, Danti, & Garbelotto, 2011;Devkota, Cornejo, Werth, Chaudhary, & Scheidegger, 2014;Gilmore et al, 2016;Zhang, Chen, Yuan, & Meng, 2015). This study focused on developing microsatellite markers based on the availability of the whole genome sequence of M. brunnea.…”
mentioning
confidence: 99%